2021
DOI: 10.4038/sljch.v50i3.9733
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory profile of children with COVID-19 admitted at a tertiary care hospital in Karnataka, Southern India

Abstract: Objectives: To assess the clinical characteristics, laboratory parameters and outcomes in paediatric patients with COVID-19. Method:Case records of all paediatric patients admitted with COVID-19 were included in the study. Data regarding mode of presentation, presence of comorbid conditions, severity of COVID-19, laboratory investigations and management were noted.Results: A total of 32 children was admitted with COVID-19 infection in our institute. COVID-19 infection was mild in 16 (50%) patients, moderate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…Severe illness was seen in about 9% of children in our study, whereas in a study by Nallasamy K, et al 11 , it was almost double. Sahana KS, et al 14 found that 25% of children had some comorbidity, which was almost similar to our study (28%) and this may be partly attributed to the fact that both studies were conducted in the same geographical area. Nallasamy K, et al 11 found that severe illnesses were more in infants with comorbidities.…”
Section: Discussionsupporting
confidence: 90%
“…Severe illness was seen in about 9% of children in our study, whereas in a study by Nallasamy K, et al 11 , it was almost double. Sahana KS, et al 14 found that 25% of children had some comorbidity, which was almost similar to our study (28%) and this may be partly attributed to the fact that both studies were conducted in the same geographical area. Nallasamy K, et al 11 found that severe illnesses were more in infants with comorbidities.…”
Section: Discussionsupporting
confidence: 90%
“…The need for invasive ventilation has ranged from 4.1 to 47% [ 11 14 , 18 , 21 , 28 , 29 ] in different studies similar to the authors’ observations. About a fifth of the children, in the present study, required noninvasive respiratory support, the need being higher particularly during the second wave.…”
Section: Discussionsupporting
confidence: 83%
“…The proportion of illness severity reported among hospitalized children greatly varies among different studies and ranges from 0.5%–79.3% for moderate, 0–42% for severe and 9%–34% for critical disease. Studies in children admitted to intensive care settings, expectedly, had a higher proportion of severe disease [ 11 , 17 , 18 , 25 – 27 ]. The interpretation of severity of illness is inconsistent, as many studies have not distinguished children with symptomatic COVID-19 from those admitted with another unrelated illness but having incidental SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%